Beyond the medical file: A scoping review on patients’ perspectives on depression treatment in primary care - Katharina Biersack; Heribert Sattel; Petra Schönweger; Lea Kaspar; Nadine Lehnen; Jochen Gensichen; Peter Henningsen (PLoS ONE, 2025)
Objectives Depressive disorders are common in the primary care setting. Despite its high prevalence, depression treatment in primary care is less guideline-oriented compared to specialized settings, which often makes it less efficient. Current research has focused on explanations on the practitioner’s side but has neglected the patient’s perspective and its effect on treatment largely. Methods We conducted a scoping review on the electronic databases Medline and Psycinfo. Eligible publications contained information of the patients’ perspective on depression treatment in primary care in OECD member states. Publications until August 2nd 2023 were considered. Results After the removal of duplicates, the search yielded 14.059 articles, of which 232 were included. Current literature focuses on behavioral and obvious measures like satisfaction, and on patient-sided barriers and facilitators to adherence. Other treatment-related behaviors are less researched. Patients with undiagnosed depression often report exclusively or mainly physical symptoms in general practice. Conclusion This review provides a comprehensive framework for the concept. Research on barriers and facilitators to depression treatment in primary care is still inconclusive. Educating patients and addressing stigmatizing beliefs are promising targets to promote the seeking out, initiation of, and adherence to treatment. Being aware of a hidden depression when somatic symptoms are present, can help to detect more cases. Registration This review is registered via OSF (https://osf.io/p9rnc).